Integrating artificial intelligence into public health education and healthcare: insights from the COVID-19 and monkeypox crises for future pandemic readiness - Abdelouahed, Mustapha; Yateem, Dana; Amzil, Chadi; Aribi, Ilyas; Abdelwahed, El Hassan; Fredericks, Salim (Frontiers in Education, 2025)
Higher education institutions are accustomed to sudden and abrupt jolts that provoke poor enrollments, unviable courses, unsustainable practices, budget cuts, and job losses. Such a situation arose with the worldwide education crisis of COVID-19 and the global mandate to shift to online teaching and learning. Policies and guidelines were based on available solutions, often implemented by leaders with limited experience in online education. As a result, the focus was on transitioning to online teaching rather than creating pragmatic policy changes. This article explores the practices in higher education institutions during the COVID-19 pandemic and investigates how the crisis affected teaching and learning across different countries. It also offers insights into the adaptations made during and after the pandemic, particularly within public health education, workforce training, and healthcare, along with actionable suggestions for integrating artificial intelligence (AI) and lessons learned from COVID-19 into these sectors. To highlight the potential benefits of AI in public health education, we discuss how AI-driven epidemiological modeling could play a crucial role in future outbreak preparedness, using the ongoing monkeypox virus (Mpox) outbreaks as a case study. As Mpox continues to emerge as a potential global health threat, the shift to remote learning during the COVID-19 pandemic has demonstrated the importance of preparing the educational system for future uncertainties, including new outbreaks. The pandemic has shown how disruptions can catalyze reforms in public health education, workforce training, and healthcare systems. Looking ahead, AI holds significant potential in transforming epidemic and pandemic preparedness by predicting outbreaks, understanding their trajectories, and even forecasting the individual impact of diseases by analyzing immune responses. Integrating AI into pandemic response frameworks could save lives and strengthen readiness for future health crises.